The defaulted sukuk - Abu Kasim, Nor Aziah; Muhamad Sohaimi, Muhamad Hishamuddin (Universiti Putra Malaysia Press, 2014)
The case focuses on the bad investment by SuciMurni of RM10 million in sukuk issued by Mercu. This was supposed to a very safe investment as Mercu had been awarded a 12-year concession for printing and sales of school textbooks. Mercu was not able to recover from its financial difficulties that led to its failure to redeem the sukuk even when the payment date was deferred twice. SuciMurni could not tolerate further default of loan repayments as it was entrusted with the use of public’s money to invest. Issues to address are, first, what went wrong, and, second, how to reduce sukuk defaults in the future. These are the imperatives of the case.